2016
DOI: 10.1039/c6ra09627a
|View full text |Cite
|
Sign up to set email alerts
|

Camphor-based CCR5 blocker lead compounds – a computational and experimental approach

Abstract: The C-C chemokine receptor type 5 (CCR5) is a transmembrane receptor that plays a pivotal role as a HIV anchor to human cell membranes, mediating viral entry. CCR5 antagonists, acting by blocking the receptor and preventing its interaction with the HIV proteins, are key agents towards effective anti-viral therapy. This work describes the computational study, synthesis and viral inhibition assay of a number of camphor derivatives as a first step towards new drug leads to block this specific entry pathway. Viral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…(1 R )-(+)-camphor ( Figure 2 ) is a natural product (also produced by synthetic means) with very ancient applications as an insect repellent, muscular relaxant, and anesthetic [ 31 , 32 ] and is currently used as a cough suppressant and decongestant according to conditions established by the Food and Drug Administration. Recent studies show that camphor derivatives may also have relevant antimicrobial [ 33 ], antiviral [ 34 , 35 ], and/or cytotoxic properties [ 36 ], being also used as photoinitiators [ 37 ] or neuro-blocking agents [ 38 ]. However, in contrast with some knowledge of silver antibacterial mechanisms, such knowledge is inexistent in the case of camphor or camphor derivatives.…”
Section: The Biological Properties Of Camphormentioning
confidence: 99%
See 1 more Smart Citation
“…(1 R )-(+)-camphor ( Figure 2 ) is a natural product (also produced by synthetic means) with very ancient applications as an insect repellent, muscular relaxant, and anesthetic [ 31 , 32 ] and is currently used as a cough suppressant and decongestant according to conditions established by the Food and Drug Administration. Recent studies show that camphor derivatives may also have relevant antimicrobial [ 33 ], antiviral [ 34 , 35 ], and/or cytotoxic properties [ 36 ], being also used as photoinitiators [ 37 ] or neuro-blocking agents [ 38 ]. However, in contrast with some knowledge of silver antibacterial mechanisms, such knowledge is inexistent in the case of camphor or camphor derivatives.…”
Section: The Biological Properties Of Camphormentioning
confidence: 99%
“…Studies carried out so far evidence that all silver camphor imine complexes display biological activity that, according to the structural and electronic characteristics of the ligands, favors antibacterial, antifungal, and/or anticancer activity [ 33 , 34 , 35 ]. In some cases, antibacterial, antifungal, and cytotoxic activity combine in the same complex [ 42 , 44 ].…”
Section: Silver Camphorimine Complexesmentioning
confidence: 99%
“…as anesthetic, muscular relaxant or insect repellent, either the compound itself or as part of natural products [ 23 25 ]. Information on the antimicrobial applications of camphor are scarce, although studies showed that camphorimine derivatives have antiviral properties against HIV [ 26 ] or influenza virus [ 27 ]. In addition, previous results obtained by us on the assessment of the antibacterial activity of camphorimine Ag(I) complexes showed that some have MIC (minimum inhibitory concentration) values considerably lower than AgNO 3 [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, this still seems one of the most promising therapeutic approaches to treat HIV-1 infection in support of the Highly Active Anti-Retroviral Therapy (HAART). 3 …”
Section: Introductionmentioning
confidence: 99%